Geometrical design of thin film photovoltaic modules for improved shade tolerance and performance. (30th August 2013) - Dongaonkar, Sourabh; Alam, Muhammad A.
Abstract Partial shading in photovoltaic modules is an important reliability and performance concern for all photovoltaic technologies. In this paper, we show how cell geometry can be used as a design variable for improved shade tolerance and performance in monolithic thin film photovoltaic modules (TFPV). We use circuit simulations to illustrate the geometrical aspects of partial shading in typical monolithic TFPV modules with rectangular cells, and formulate rules for shade tolerant design. We show that the problem of partial shading can be overcome by modifying the cell shape and orientation, while preserving the module shape and output characteristics. We discuss two geometrical designs with cells arranged in radial and spiral patterns, which (i) prevent the reverse breakdown of partially shaded cells, (ii) improve the overall power output under partial shading, and (iii) in case of spiral design, may additionally improve the module efficiency by reducing sheet resistance losses. We compare these designs quantitatively using realistic parameters and discuss the practical aspects for their implementation. Copyright © 2013 John Wiley & Sons, Ltd.